Sleep, nutritional status and eating behavior in children: a review study - Hermes,Fernanda Nascimento (2022)
ABSTRACT Objective: To review the current literature on the relationship between sleep, nutritional status and eating behavior, as well as mechanisms associated with these elements in children. Data source: The literature research was conducted in the PubMed, LILACS and Scopus databases, using the following terms: “Child”; “Nutritional status”; “Sleep”; “Physical activity OR Physical activities OR Exercise”. The articles included were those that met the research objective. Review articles, letters to authors, or guidelines were excluded. Data synthesis: 402 articles were initially found in the literature search. After careful analyses of the title and abstract, and application of inclusion criteria, only 24 studies were included in the present review. Most studies (n=13) suggest that short sleep duration (<9-10 hours/night) is associated with overweight/obesity in children. Only three studies did not show associations between overweight/obesity and sleep variables. Short sleep duration is also associated with poor food quality, higher intake of soft drinks and stimulant beverages before bedtime, as well as micronutrient deficiency. Conclusions: Sleep duration is related to overweight and obesity development in infants. Changes in dietary pattern are also related to sleep debt, being one of the mechanisms that contribute to excessive weight gain. It is necessary that health professionals understand the importance of sleep quality in the nutritional status maintenance in children.